2003
DOI: 10.1080/02640410310001641395
|View full text |Cite
|
Sign up to set email alerts
|

Acute impact of submaximal resistance exercise on immunological and hormonal parameters in young men

Abstract: In this study, we examined the acute effects of submaximal resistance exercise on immunological and hormonal parameters in 7 resistance-trained and 10 non-resistance-trained males. The participants, who were aged 29.5 +/- 7.1 years (mean +/- s), performed submaximal resistance exercise at 75% of their one-repetition maximum. Blood samples were taken before, during, immediately after, and 30, 60 and 120 min after exercise and analysed for leukocyte subpopulations and stress hormones. Total leukocytes, neutrophi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
25
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 39 publications
5
25
1
1
Order By: Relevance
“…The possible reasons for the present Wnding may be the timing of the blood samples in design IV (from 0 to 30 min and 48 h post-RE) and the fact that the post-RT exercise workout was with the same relative, not absolute, workload than the pre-RT exercise workout unlike in the 'repeated-bout eVect' studies using two exercise sessions separated by few weeks (Pizza et al 1996). In agreement, RE-induced blood leukocytosis has been previously reported to be similar in untrained and trained young males in a cross-sectional design (Ramel et al 2003) and also not to be substantially aVected from 10 weeks of RT in older women (McFarlin et al 2005).…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The possible reasons for the present Wnding may be the timing of the blood samples in design IV (from 0 to 30 min and 48 h post-RE) and the fact that the post-RT exercise workout was with the same relative, not absolute, workload than the pre-RT exercise workout unlike in the 'repeated-bout eVect' studies using two exercise sessions separated by few weeks (Pizza et al 1996). In agreement, RE-induced blood leukocytosis has been previously reported to be similar in untrained and trained young males in a cross-sectional design (Ramel et al 2003) and also not to be substantially aVected from 10 weeks of RT in older women (McFarlin et al 2005).…”
Section: Discussionsupporting
confidence: 79%
“…In a recent study with elderly women a short bout of RE did not induce blood leukocytosis immediately post-RE or at later time-points (Neves Sda et al 2009) and this is in contrast to large number of studies with young or middle-aged subjects (Nieman et al 1995;Kraemer et al 1996;Natale et al 2003;Ramel et al 2003;Risoy et al 2003;Simonson and Jackson 2004;Mayhew et al 2005). The present study, however, showed that with large enough exercise volume and intensity, the blood leukocytosis occurs also in older subjects agreeing with a study in older women (McFarlin et al 2005).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…61 Following an acute bout of resistance exercise, Natural Killer cells, and phagocytes (monocytes and neutrophils) increase in the circulation whereby the number of some of these subsets (monocytes, neutrophils) remain elevated for up to 2 h postexercise. 62 The duration and magnitude of the post exercise leukocytosis is diminished in the older population as a consequence of age-related decline in leukocytes. 61 with total exercise time as low as ~ 10 min.…”
Section: The Immune Systemmentioning
confidence: 99%